A clinical perspective on adipose‐derived cell therapy for enhancing microvascular health and function: Implications and applications for reconstructive surgery. (29th November 2020) - Jones, V. Morgan; Suarez‐Martinez, Ariana D.; Hodges, Nicholas A.; Murfee, Walter L.; Llull, Ramon; Katz, Adam J.
Abstract: Restoration of form and function requires apposition of tissues in the form of flaps to reconstitute local perfusion. Successful reconstruction relies on flap survival and its integration with the recipient bed. The flap's precariously perfused hypoxic areas undergo adaptive microvascular changes both internally and in connection with the recipient bed. A cell‐mediated, coordinated response to hypoxia drives these adaptive processes, restoring a tissue's normoxic homeostasis via de novo vasculogenesis, sprouting angiogenesis, and stabilizing arterialization. As cells exert prolonged and coordinated effects on site, their use as biological agents merit translational consideration of sourcing angio‐competent cells and delivering them to territories enduring microcirculatory acclimatization. Angio‐competent cells abound in adipose tissue: a reliable, accessible, and expendable source of adipose‐derived cells (ADC). When subject to enzymatic digestion and centrifugation, adipose tissue separates its various ADC: A subset of buoyant oil‐dense adipocytes (the tissue's parenchymal component) accumulates on a supra‐natant layer, whereas the mesenchymal component remains in the infra‐natant sediment, containing the tissue's stromal vascular fraction (SVF), where angio‐component cells abound. The SVF can be further manipulated, selected, or culture expanded into more specific stromal subsets (herein defined as adipose stromal cells, ASC). While promising clinical applications for ADC await clinical proof and regulatory authorization, basic science investigation is needed to elucidate the specific ADC mechanisms that influence microvascular growth, remodeling, and function following flap surgery. The objective of this article is to share the clinical perspectives of reconstructive plastic surgeons regarding the use of ADC‐based therapies to help with flap tissue integration, revascularization, and wound healing. Specifically, the focus will be on considering the potential for ADC as therapeutic agents and how their clinical application motivates basic science opportunities.